POLITICAL PARTY PROPAGANDA IN DKI JAKARTA LOCAL ELECTION 2017 IN ONLINE MEDIA (CONTENT ANALYSIS POLITICAL PARTY PROPAGANDA IN DKI JAKARTA LOCAL ELECTION 2017 IN KOMPAS.COM) - Mikha Christian H; Much. Yuliyanto, S.Sos, M.Si (Interaksi Online, 2016)
To reach its target, the political parties so as to package the message propagated. In the event the local elections DKI 2017, in an effort to get a seat regional head not inevitable then the propaganda is played by political parties. The purpose of this study was to determine the form of propaganda made by the political parties in local elections in 2017 DKI Media Online (Kompas.com). This research is a quantitative research using content analysis method with descriptive approach. To view the propaganda of this study are categorized kind of propaganda is hidden, open, vertical, horizontal and techniques of propaganda, name calling, glittering generalities, testimonials, transfer, plain folk, card stacking, bandwagon technique, reputable mouthpiece and using all forms of persuations. The recording unit of this study is an excerpt and image. After doing Coding, it was found that the most frequent Gerindra hidden propaganda that as many as 26 times, vertical propaganda as much as 26 times, and most frequently used techniques in their delivery Card Stacking in Kompas.com. Through the PPP Coding also found that the most frequently hidden propaganda that as many as 49 times, 49 times vertically, and the most frequently used technique Card Stacking ie as many as 23 times in Kompas.com. The use of propaganda techniques hidden impact to people who receive propaganda. By presenting a one-sided even using a falsehood, society becomes tercerdaskan in understanding the situation and take a decision. Mechanical testimony is unlikely to exist in a daily news excerpts. Can the emergence of this technique requires a propagandist flexibility in determining the content of the communication media with which to spread the message. With the limitation provisions of the news content, a propagandist would be difficult to use the techniques of propaganda in the news daily. Even if there is a statement from a figure reported by the authors, it will be difficult to identify the interested figure behind the deposit of the statement